Spin-wave modes of magnetic bimerons in nanodots. (1st July 2022) - Jin, Chendong; Li, Shuang; Zhang, Hu; Wang, Ruining; Wang, Jianglong; Lian, Ruqian; Gong, Penglai; Shi, Xingqiang
Abstract: We report the resonance excitations and the spin-wave modes of a single bimeron in a confined nanodot by using micromagnetic simulations. Magnetic bimerons can be considered as in-plane topological spin textures of magnetic skyrmions, which means that the spin-wave modes of bimerons also rotate in-plane compared to skyrmions, for example, through the application of out-of-plane microwave magnetic fields, the spin-wave mode of bimerons is no longer a breathing mode but contains a counterclockwise mode at low frequencies and a clockwise mode at high frequencies. When in-plane microwave magnetic fields rotated at different angles are applied, the spin-wave mode of bimerons has an anisotropic property, i.e., the spin-wave mode presents as a breathing mode for the microwave magnetic field applied along the x -direction, and a couple of azimuthal modes for the microwave magnetic field applied along the y -direction. Moreover, we demonstrate that the breathing mode, the counterclockwise rotation mode, and the clockwise rotation mode can simultaneously appear together when the microwave magnetic field is applied at a specific angle in the plane. In addition to the three typical spin-wave modes, two high-phase counterclockwise rotation modes lead to the periodic deformation of bimerons due to the broken rotational symmetry of the spin texture. Our results reveal the rich spin-wave modes of bimerons, which may contribute to the applications in spintronics and magnonics.